Representative misconduct, voter perceptions and accountability: Evidence from the 2009 House of Commons expenses scandal - Vivyan, Nick; Wagner, Markus; Tarlov, Jessica (Electoral Studies, 2012)
This paper examines electoral accountability after the 2009–10 UK expenses scandal. Existing research shows that Members of Parliament (MPs) implicated in the scandal fared only marginally worse in the election than non-implicated colleagues. This lack of electoral accountability for misconduct could have arisen either because voters did not know about their representative's wrongdoing or because they chose not to electorally sanction them. We combine panel survey data with new measures of MP implication in the expenses scandal to test where electoral accountability failed. We find that MP implication influenced voter perceptions of wrongdoing more than expected. In contrast, constituents were only marginally less likely to vote for MPs who were implicated in the scandal. Electoral accountability may therefore be constrained even when information about representative misconduct is easily available and clearly influences voter perceptions.
EPrint Processing Status: Full text deposited in DRO
Keywords: Accountability; Expenses scandal; Information; Members of Parliament; Voting behaviour.